(3QYGjI GdaFGJ GdNGUI (B/s - (3GdHdhj, SdGeI eMeO SdeGf GdgQaj,s 1957- ((3GdTGQbI, GdEeGQGJ GdYQHjI GdeJMOI (B:s (3ecJHI GdUMGHI (B:s (3GdbGgQI (B:s (3ecJHI GdJGHYjf,s, 2003)
(3jJfGhd cJGH (B((3QYGjI GdaFGJ GdNGUI(B) (3hGdPj bGe HJCdjag O(B. (3SdGeI eMeO GdgQaj GdHdhj, ehVhY (B((3GGdaFGJ GdNGUI(B) (3GdcJGH jhVM fXQI GdMVGQI GdESdGejI ddaFGJ GdNGUI (B((3CUMGH GdYGgGJ, hGddbWGA, hcHGQ GdSf, hGdRefi(B) (3fXQI JbOjQ hGMJQGe, JfHY ef GdCSGS GdPj bGeJ Ydjg GdMVGQI GdESdGejI(B. (3hCf GdOSJhQ GdMVGQj GdESdGej GdNGdO (B((3GdbQBf hGdSfI(B)(3, de jJQc CeQgG ddGLJgGOGJ GdaQOjI, Hd fU Hcd hVhM Ydi VQhQI GdYfGjI HgG OjGfI hEfSGfjI, hGYJHQgG EMOi GdWQb GdehUdI deQVGI Gddg hQShdg, hhGLH QYGjI gPg GdaFGJ QYGjI TehdjI eY OeLge aj GdeLJeY, heYGedJge Ydi bOe GdeSGhGI eY ZjQge ef YfGUQ GdeLJeY(B. s
Keywords: (3GdESdGe hPhj Gdgees; (3Phj Gdgees -- (3QYGjIs; (3GdESdGe hGdNOeI GdGLJeGYjIs